Application of simultaneous engineering in the machines construction by Ecuador’s metalmechanical mipymes - Erazo Arteaga, Víctor Alfonso; Mejía Echeverría , Cosme Damián; Valencia Aguirre, Fernando Vinicio; Terán Pineda, Diego Francisco (I+ T+ C- Research, Technology and Science, 2017)
In Ecuador, micro, small and medium-sized enterprises (MIPYMES) of the metal-mechanical sector that are dedicated to the construction of machinery for processing and packaging of products, have handmade manufacturing. The high rate of imports of these devices demonstrates the distrust that the consumers have in the local market. This document proposes a methodology of design and manufacturing that takes as a principle the simultaneous engineering, aims to demonstrate the benefits of implementing design methodologies through the optimization of manufacturing times. A case is studied about its design and construction of the filling machine of gelatin. Analyzing its operation, alternative solutions are proposed and the detailed engineering is summarized. The results of the execution of this system are presented, after having been implemented for 15 months in a metalworking company that is dedicated to this activity, concluding that the manufacturing times is reduced to 32% as the main result.